A Model-Based Systems Engineering Approach to the Development of a Space-Based Observatory for NEO Detection (2025)
A Near-Earth Object (NEO) is an asteroid or comet with a perihelion distance of less than 1.3 AU from the Sun that approaches the vicinity of Earth. This implies that one of these objects could intersect the Earth’s trajectory and potentially impact our planet. Many asteroids within this group have not yet been detected, either due to their small size or because their trajectory approaches from the direction of the Sun, which limits ground-based telescope observations. Considering the advantages of space observations, such as the absence of atmospheric interference, no obstruction from satellites and space debris, and reduced background interference from Earth, this thesis proposes the conceptual design of a space-based observatory capable of detecting and monitoring NEOs that are extremely difficult to detect from the ground. To achieve this, a Model-Based Systems Engineering (MBSE) approach is proposed, starting from the definition of the operational concept and system requirements, through the design of the physical architecture. This approach enables the use of digital tools to optimize the design of complex systems, such as the proposed observatory.